Unraveling the genetic potential of Indian rice germplasm for reproductive stage drought tolerance - Santhiya Subramanian; Pushpam Ramamoorthy; Subramanian Alagesan; John Joel Amalraj; Raveendran Muthurajan; Senthil Alagarsamy; Muthuramu Sengalan; Suresh Ramalingam; Pravin Kumar Kathiresan; Parthiban Thathapalli Prakash (Frontiers in Plant Science)
Climate change poses a serious threat to future food security on a global scale. Drought is the most challenging abiotic stress, limiting rice production in rainfed rice ecosystems. Therefore, an experiment was designed under three distinct environments, non-stress irrigated condition, managed stress condition (Rainout shelter) and natural stress condition (Target Population of Environment) involving 500 Indian rice germplasms. The study aimed to assess the genetic differences, drought tolerance behavior and to identify potential drought-tolerant donors for climate-resilient drought breeding. The results revealed that yield-attributing and physiological traits were affected by drought stress, resulting in a grain yield reduction of 64.30% in managed stress condition and 68.12% in natural stress condition. A high heritability estimate for most of the traits under non-stress and stress conditions indicates that selection for grain yield under stress conditions can be done with the same precision as in non-stress condition. Mixed linear model revealed a considerable genetic variation for yield and yield-attributing traits. The correlation between the environments was found positive for the traits studied. Multi-environment trait association revealed that panicle weight, spikelet fertility and number of productive tillers per plant are the key pre-breeding traits for grain yield improvement under drought. Multi-environment analysis identified 47 accessions with yield superiority over the drought-tolerant checks. Multi-trait selection index reaffirmed that RL 4167, RL 6361 and RL 4131 are drought tolerant and high yielding under multi-environment analysis. Therefore, the promising high yielding accessions viz., RL 4167, RL 6361, RL 4131, RL 27 and RL 6298, thus identified, could serve as potential donors for grain yield improvement under drought stress.